Let's solve the compound inequality step by step:
The compound inequality given is: \[ -2 \leq 2x + 13 - 4 < 1 \]
First, we can simplify the middle part: \[ 2x + 13 - 4 = 2x + 9 \]
So the compound inequality now looks like this: \[ -2 \leq 2x + 9 < 1 \]
Now we can split this into two separate inequalities to solve them one at a time.
1. Solve \(-2 \leq 2x + 9\)
Subtract 9 from both sides: \[ -2 - 9 \leq 2x \] \[ -11 \leq 2x \]
Now, divide both sides by 2: \[ -\frac{11}{2} \leq x \] or equivalently, \[ x \geq -\frac{11}{2} \]
2. Solve \(2x + 9 < 1\)
Subtract 9 from both sides: \[ 2x < 1 - 9 \] \[ 2x < -8 \]
Now, divide both sides by 2: \[ x < -4 \]
Combined Solution
The two parts of the compound inequality give us: \[ -\frac{11}{2} \leq x < -4 \]
We can convert \(-\frac{11}{2}\) to a decimal to make it easier to see the ranges: \(-\frac{11}{2} = -5.5\)
So, the combined solution is: \[ -5.5 \leq x < -4 \]
In interval notation, this would be expressed as: \[ [-5.5, -4) \]
This interval represents the solution to the original compound inequality.